The practice of chest radiography using different digital imaging systems: Dose and image quality - Moey, Soo Foon; Zubir, Ahmad Shazli; Sayed, Inayatullah Shah (Iranian Association of Medical Physicists, 2018)
Introduction: The study was undertaken to evaluate the practice of chest radiography using different digital imaging systems and its influence on dose and image quality. Materials and Methods: The study was carried out in two hospitals from March 2016 to June 2016. Sixty ambulatory patients aged 21 to 60 years who were able to cooperate without difficulty and weighed between 60 to 80 kg were selected randomly. The active matrix flat panel imagers technology was employed in the direct radiography (DR) system for Hospital A, whilst Hospital B used the single read out computed radiography (CR) system. The dose area product (DAP) meter was utilized in measuring the entrance surface air kerma. The chest radiographs were evaluated by two radiologists. Results: The mean entrance surface doses (ESDs) for posteroanterior chest in Hospital A (0.098 mGy) was lower than that obtained in Hospital B (0.161 mGy). However, the ESDs at both centres were lower than the recommended value by the International Atomic Energy Agency (IAEA; 0.3 mGy). The quality of the images for chest radiography in both hospitals was adequate to make a diagnosis with ESDs and effective doses lower than those recommended by IAEA and United Nations Scientific Committee on the Effects of Atomic Radiation (UNSCEAR). Conclusion: The study serves to highlight the practice of chest radiography with two different systems and its influence on image quality and dose. It can be concluded that there were significant differences in image quality and radiation dose for chest radiography practice using CR and DR.